Manajemen Komunikasi Sosial Penganut Agama Baha’i - Umi Rojiati (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2019)
This study aims to obtain an overview of Religious Experience. Principles of Baha'i Trust and Social Communication. Dogma and Baha'i Trust in Influencing Social Communication of Followers and Social Communication of Adherents of the Baha'i Religion with the Neighborhood Community. This research uses phenomenological methods and theories, qualitative approaches. The results of the study show that the essence of religious experience, namely sensitivity to the sacred, the religious experience is not only natural but also cultural. The Baha'i believe that God is the Creator of the universe, the apostles and prophets are intermediaries to channel God's will for humans through divine revelation contained in the holy books of various religions in the world. The purpose of the Baha'i religion is to realize spiritual transformation in human life and renew the institutions of society based on principles to the Essence of God, the unity of religion, and the unity of all humanity. From some of the teachings, goals, and visions of the Baha'i, the Baha'is in Bandung transformed themselves through their daily attitudes that are always friendly to everyone and open to the local community.Penelitian ini bertujuan untuk memperoleh gambaran mengenai Pengalaman Keagamaan. Asas-asas Kepercayaan Baha’i dan Komunikasi Sosial. Dogma dan Kepercayaan Baha’i dalam Mempengaruhi Komunikasi Sosial Para Pengikutnya dan Komunikasi Sosial Penganut Agama Baha’i dengan Masyarakat Sekitar. Penelitian ini menggunakan metode dan teori fenomenologi, pendekatan kualitatif. Hasil penelitian menunjukan bahwa, Hakikat pengalaman keagamaan, yaitu kepekaan terhadap yang suci, maka pengalaman religious bukan hanya natural tetapi juga kultural. Umat Baha’i percaya bahwa Tuhan adalah Sang Pencipta alam semesta, para rasul dan nabi merupakan perantara untuk menyalurkan kehendak Tuhan bagi manusia melalui wahyu Illahi yang terdapat dalam kitab-kitab suci berbagai agama di dunia. Tujuan agama Baha’i adalah untuk mewujudkan transformasi rohani dalam kehidupan manusia dan memperbaharui lembaga-lembaga masyarakat berdasarkan prinsip-prinsip ke Esaan Tuhan, kesatuan agama, dan persatuan seluruh umat manusia. Dari beberapa ajaran, tujuan dan visi umat Baha’i tersebut, para penganut Baha’i di Bandung mentransformasikannya lewat sikap mereka sehari-hari yang selalu ramah kepada setiap orang dan terbuka terhadap masyarakat setempat.